1984
DOI: 10.1002/chin.198401332
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF ORALLY ACTIVE CARDIOSTEROID DERIVATIVES

Abstract: Das aus dem Steroidalkohol Hellebrigcnin (I) mit Chloracctylchlorid (II) zugängliche α‐Chloroucctat (III) läßt sich mit dem Dimethylmorpholin (IV) zum Morpholinoacctat (V) umsetzen, mit den Carbonsäurechloriden (VIa) bzw. Anhydridcn (VIa) werden die Ester (VII) erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We therefore prepared various new compounds: Compounds 4and 7 are more hydrophilic due to the substitution by a glyceryl or a pyranosyl residue. Compound 5 was constructed in view of the demonstration with cardiotonic steroids that the dimethylacryloylester derivative was as potent as the hellebrigenine heterosids (11). Our results showed that none of the derivatives were more active than forskolin.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We therefore prepared various new compounds: Compounds 4and 7 are more hydrophilic due to the substitution by a glyceryl or a pyranosyl residue. Compound 5 was constructed in view of the demonstration with cardiotonic steroids that the dimethylacryloylester derivative was as potent as the hellebrigenine heterosids (11). Our results showed that none of the derivatives were more active than forskolin.…”
Section: Resultsmentioning
confidence: 87%
“…To a solution of 2 (18 mg) in anhydrous CH2CI2 (2 ml) was added freshly distilled dimethylacryloyl chloride (0.02 ml). The solution was refluxed under N2 for 1.5 hour and allowed to stand at room temperature for 4 hours (11). The solution was then diluted with CH2CI2 (10 ml) washed with a saturated NaHCO3 solution (3 x 10 ml) and with water (10 ml).…”
Section: 3-o-isopropylidene-o-glyceric Acidmentioning
confidence: 99%
“…All were highly active, and the dimethylacrylate appeared to have a better therapeutic index than conventional cardiac glycosides. 208 The furan (162) and the butenolide (163)…”
Section: Androstanes and Oestranesmentioning
confidence: 99%